CXCR4 signaling at the fetal–maternal interface may drive inflammation and syncytia formation during ovine pregnancy. Issue 2 (3rd November 2020) - McIntosh, Stacia Z; Maestas, Marlie M; Dobson, Jordyn R; Quinn, Kelsey E; Runyan, Cheyenne L; Ashley, Ryan L
Abstract: Early pregnancy features complex signaling between fetal trophoblast cells and maternal endometrium directing major peri-implantation events including localized inflammation and remodeling to establish proper placental development. Proinflammatory mediators are important for conceptus attachment, but a more precise understanding of molecular pathways regulating this process is needed to understand how the endometrium becomes receptive to implantation. Both chemokine ligand 12 (CXCL12) and its receptor CXCR4 are expressed by fetal and maternal tissues. We identified this pair as a critical driver of placental angiogenesis, but their additional importance to inflammation and trophoblast cell survival, proliferation, and invasion imply a role in syncytia formation at the fetal–maternal microenvironment. We hypothesized that CXCL12 encourages both endometrial inflammation and conceptus attachment during implantation. We employed separate ovine studies to (1) characterize endometrial inflammation during early gestation in the ewe, and (2) establish functional implications of CXCL12 at the fetal–maternal interface through targeted intrauterine infusion of the CXCR4 inhibitor AMD3100. Endometrial tissues were evaluated for inflammatory mediators, intracellular signaling events, endometrial modifications, and trophoblast syncytialization using western blotting and immunohistochemistry. Endometrial tissue from ewes receiving CXCR4 inhibitor demonstrated dysregulated inflammation and reduced AKT and NFKB, paired with elevated autophagic activity compared to control. Immunohistochemical observation revealed an impairment in endometrial surface remodeling and diminished trophoblast syncytialization following localized CXCR4 inhibition. These data suggest CXCL12–CXCR4 regulates endometrial inflammation and remodeling for embryonic implantation, and provide insight regarding mechanisms that, when dysregulated, lead to pregnancy pathologies such as intrauterine growth restriction and preeclampsia. Abstract : Summary Sentence Disrupting intrauterine CXCR4 signaling during trophoblast attachment impairs syncytia formation, endometrial gland inflammation, and associated intracellular signaling.